EMG characteristics and fibre composition: study on rectus femoris of sprinters and long distance runners - Goswami, A.; Sadhukhan, A. K.; Gupta, S. (Indian Journal of Physiology and Pharmacology, 2001)
The study was conducted on 9 sprinters and 5 long distance runners to investigate the difference in power spectral characteristics of rectus femoris muscle and the feasibility of using electromyographic techniques in categorization of muscle groups in slow dominant and fast dominant types. EMG signal was recorded, after digitization at 4 KHz, from rectus femoris muscle during isometric knee extension (at maximum voluntary contraction level) until fatigue. Digitized signal was processed for Fast Fourier Transform and Root Mean Square (RMS) voltage. Significant difference (P < 0.05) was found in RMS voltage between sprinters and long distance runners. Both groups showed decline in Mean Power Frequency (MPE) and rate of decline in sprinters was rapid. Normalized MPF showed better discrimination between the two groups. It is concluded that the EMG response observed in this study was possibly a result of differences in the muscle fibre composition of the athletes. EMG study using spectral characteristics would be useful in categorizing the sports persons in terms of suitability of the events.